Nutrition transition in Zambia: Changing food supply, food prices, household consumption, diet and nutrition outcomes - Harris, J.; Chisanga, B.; Drimie, S.; Kennedy, G. (Springer, 2019)
The nutrition transition literature has generally drawn on epidemiologic and demographic changes to make its argument, because in many cases broader data are not available on the drivers of nutrition change. Going further, this paper draws on wider food systems literature, and includes food price and expenditure data, to join the dots from macroeconomic and food system change to food sources, production, and price; to household-level expenditures; to changing diets and nutrition and health outcomes, illustrated through the case of Zambia. Many of the economic and demographic drivers of the nutrition transition are present in Zambia, including rising GDP, high urbanization and increasing supermarket penetration. Food supply data show a reduction in calories available per capita over several decades, and low levels of nutrient-rich plant and animal source foods which make up a diverse, nutritious diet. National food price data show that while the cost of food has reduced overall, nutrient-rich foods are more expensive relative to staple foods over time. Expenditure on staple foods has reduced in the past two decades while spending on fruits and vegetables, animal source foods, fats and sugars, and processed foods has increased, with these change greater in rural areas in recent years, but already more advanced in urban areas. Finally, while undernutrition is reducing slowly from very high levels and hunger persists, overweight and obesity and non-communicable chronic diseases are increasing; and data are strikingly lacking on modern Zambian diets. The Zambia case study is placed within regional and global trends to illustrate nutrition transition changes that are now happening in rapidly changing lower-middle income countries. Policy responses include promoting the availability of diverse nutrient-dense foods, and concurrent attention to preventing under- and over-nutrition in surveillance and policy. This paper also sheds light on the gaps in information that would greatly improve our understanding of the food system drivers of the nutrition transition, and hence our ability to create relevant policy.